2017
DOI: 10.1080/08869634.2017.1292175
|View full text |Cite
|
Sign up to set email alerts
|

Age, gender and parafunctional habits as prognostic factors for temporomandibular joint arthrocentesis

Abstract: Arthrocentesis is an effective management method for symptomatic patients with ADDWOR at one-month post treatment, especially in the absence of parafunctional habits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 31 publications
3
9
0
7
Order By: Relevance
“…Similarly, Kim et al found that the success rate of arthrocentesis in patients in their fifties or older is likely to be low. Their results were consistent with the previous studies of Von Korff et al and Attia et al On the contrary, Nishimura et al found no significant relationship between the age and the success rate of the arthrocentesis . Consistent with the Nishimura et al, we found no correlation between the age and the success of the procedure.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, Kim et al found that the success rate of arthrocentesis in patients in their fifties or older is likely to be low. Their results were consistent with the previous studies of Von Korff et al and Attia et al On the contrary, Nishimura et al found no significant relationship between the age and the success rate of the arthrocentesis . Consistent with the Nishimura et al, we found no correlation between the age and the success of the procedure.…”
Section: Discussionsupporting
confidence: 93%
“…The standard deviation of the post-operative MMO and VAS were assumed to be the same as the pre-operative values. In 3 of the studies, arthrocentesis was performed as the initial treatment for TMDs [20][21][22][23] , in 2 of the studies, arthrocentesis was done within 3 months of failing conservative treatment 24,25 , and in 5 of the studies, arthrocentesis was performed after at least 3 months of conservative treatment [26][27][28][29][30] . Both random effects model and fixed effects models were used for construction of forest plots, due to the intention of generalization inference and the high heterogeneity found in the included studies, but also because of the small number of studies included in the meta-analysis.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…In 2 of the studies 24,25 , arthrocentesis was performed within 3 months of failing conservative treatment (2 weeks and 1 month). In the other 5 studies [26][27][28][29][30] , arthrocentesis…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations